1994
DOI: 10.1002/hep.1840200416
|View full text |Cite
|
Sign up to set email alerts
|

Soluble intercellular adhesion molecule-1 in primary biliary cirrhosis: Relationship with disease stage, immune activity and cholestasis

Abstract: Intercellular adhesion molecule-1, strongly expressed on the interlobular and proliferating bile ducts in primary biliary cirrhosis, is important in the migration and adhesion of inflammatory cells from the circulation to these structures. A soluble form has been found to be elevated in serum in primary biliary cirrhosis. Our aim was to check on the role of soluble intercellular adhesion molecule-1 in primary biliary cirrhosis with particular reference to its specificity by comparison with other disease contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
10
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 35 publications
3
10
0
Order By: Relevance
“…In agreement with previous reports (28,29), we have found that serum concentrations of soluble forms of ICAM-1 and E-selectin are significantly elevated in PBC patients relative to normal subjects. Although similar to levels measured in CH subjects, in PBC they are highly increased as compared to those detected in cirrhotic patients.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with previous reports (28,29), we have found that serum concentrations of soluble forms of ICAM-1 and E-selectin are significantly elevated in PBC patients relative to normal subjects. Although similar to levels measured in CH subjects, in PBC they are highly increased as compared to those detected in cirrhotic patients.…”
Section: Discussionsupporting
confidence: 93%
“…This may reflect upregulated expression of adhesion molecules on bile ducts, hepatocytes, vascular endothelial cells, and infiltrating leukocytes, a critical step in the pathogenesis of immunemediated destruction of interlobular bile ducts and hepatocytes (3,6). Although not specific to PBC, increased serum levels of circulating forms of adhesion molecules have been correlated with the stage of progression of the disease (9,10,29). Indeed, this is supported by relationships between soluble adhesion molecules and biochemical markers of cholestasis in our study.…”
Section: Discussionsupporting
confidence: 75%
“…Adams et al hy-and secretion of an alternatively spliced form of ICAM-1 as a possibility 22 or the general shedding/cleavage of pothesized that sICAM-1 may be derived from activated lymphocytes accumulated in the liver, 23 however, the extracellular domain of ICAM-1 from the surface of parenchymal cells and vascular endothelial cells in lymphocyte activation does not always correlate with serum levels of sICAM-1. 26 Moreover, in our experi-the liver and extrahepatic tissue. [28][29][30][35][36][37] The latter mechanism is unlikely the result of cell injury because mental model, neutrophils and not lymphocytes are the cytotoxic cell type in the liver 3 suggesting that liver the highest serum levels and biliary efflux rates were measured without liver injury and even in the galactoscells other than lymphocytes have to be the source of sICAM-1.…”
Section: Discussionmentioning
confidence: 91%
“…22 Subsequent investigations indicated that plasma levels of sICAM-1 are elevated in most inflamAbbreviations: ICAM-1, intercellular adhesion molecule 1; mRNA, messenger RNA; sICAM-1, soluble ICAM-1; PBS, phosphate-buffered saline; TNF-a, matory liver diseases in humans. [23][24][25][26] The hypothesis tumor necrosis factor a; IL-1, interleukin-1.…”
mentioning
confidence: 99%
See 1 more Smart Citation